Passage of Time Judgments Are Not Duration Judgments: Evidence from a Study Using Experience Sampling Methodology - Droit-Volet, Sylvie; Wearden, John (Frontiers in Psychology, 2016)
This study examined relations between passage of time judgments and duration judgments in everyday life, in young and elderly people, with an Experience Sampling Method (ESM). The duration judgments were assessed by verbal estimation and interval production measures. The results showed no difference between young and elderly people in judgments of rate of passage of time, a result contrary to the conventional idea that time passes more quickly as we get older. There were also no significant relation between the judgment of passage of time and the judgments of durations. In addition, the significant predictors of individual differences in the judgment of passage of time (emotion states and focus of attention on the current activity) were not predictors of judgment of durations. In sum, passage of time judgments are not related to duration judgments.